Opposition party organizational features, ideological orientations, and elite co-optation in electoral autocracies. Issue 4 (19th May 2022) - Kavasoglu, Berker
ABSTRACT: Autocrats often attempt to co-opt select opposition party leaders to remain in power. While the literature identifies co-optation of opposition party leaders as an important survival strategy of autocrats, we lack a systematic examination of why some opposition party leaders are co-opted but not others. This article argues that opposition party co-optation is shaped by both inter- and intra-party dynamics. Using a novel data set on opposition party organizations in electoral autocracies between 1970 and 2019, I show that opposition parties with high mobilizational capacity and those that devolve internal decision-making authority from the party leadership to lower cadres are less likely to be co-opted, especially when they are ideological distant from autocratic incumbents. I contend that opposition parties' organizational characteristics and their ideological positioning in an autocratic party system significantly alter the strategic calculus of the incumbent regime and opposition party elites in deciding whether or not to cooperate with one another. Hence, autocratic incumbents' ability to control opposition parties through co-optation is shaped not only by the commonly highlighted factors such as resource availability, institutional manipulation or repression, but also as a result of the relatively less well-understood factors such as opposition party organizational features and party positions.